Assessing the impact of deficit irrigation strategies on agronomic and productive parameters of Menara olive cultivar: implications for operational water management - Ibba, Khaoula; Kassout, Jalal; Boselli, Vladimiro; Er-Raki, Salah; Oulbi, Sara; Mansouri, Loubna El; Bouizgaren, Abdelaziz; Sikaoui, Lhassane; Hadria, Rachid (Frontiers in Environmental Science, 2023)
The olive tree is an iconic tree in the Mediterranean region, traditionally cultivated under rainfed conditions, but olive cultivars are also found outside the Mediterranean and are widely used for oil and olive production. However, with the increasing aridity and global changes olive agroecosystems are facing sustainability challenges. This study aims to evaluate the effect of two deficit irrigation strategies on the agronomic and productive parameters of the Menara olive cultivar as a tool for operational irrigation water management. For this purpose, an experiment was conducted on an olive orchard for two consecutive years (2021 and 2022), comparing four regulated deficit (RDI) treatments and two sustained deficit (SDI) treatments, with a fully irrigated trees. The results showed that moderate and controlled water stress under the RDI did not significantly affect the yield of the Menara olive. In addition by reducing plant water requirement by 20% during sensitive periods and by 40% during normal periods, under RDI, it is possible to save between 25% and 30% of irrigation water and to increase water productivity by 5% to 20% with a slight decrease in fruit yield ranging between 10% and 15%. However, the trees subjected to the SDI strategy exhibited a reduced capacity for shoot growth when compared to those under RDI and fully irrigated (FI) conditions. Our findings showed that water deprivation during sensitive periods reduced phenological traits and slowed down shoot growth. Furthermore, the water status of trees was reflected in fruit volume, as a decrease in water supply resulted in a corresponding reduction in the fruit volume. Although the study provides important insights into water management strategies for olive cultivation, the short observation period does not allow for long-term plant adaptation evaluation and productivity beyond two years. Therefore, it is recommended that future studies extend the observation period to better understand plant adaptation to irrigation regimes.